2019
DOI: 10.4236/wjet.2019.72016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Turbulence Models on Bridge-Pier Scour Using Flow-3D

Abstract: The main purpose of this paper is to analyze the influence of different turbulence flow models on scouring pit of bridge-pier. Flow-3D software is applied in line with the purpose. The key motivation for this study is to contribute to the Flow-3D software by means of some modification and adjustment in the sediment scour model and shallow water model. An assessment of turbulence model adopted with the parameters of the Melville experiment to estimate the maximum scour-depth was performed. In the simulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For three-dimensional analysis of an incompressible fluid state within the Flow-3D software, the Reynolds-Averaged Navier-Stokes (RANS) equations in the Cartesian coordinate system are employed, as outlined by (Man et al 2019):…”
Section: Reynolds Average Navier-stokesmentioning
confidence: 99%
“…For three-dimensional analysis of an incompressible fluid state within the Flow-3D software, the Reynolds-Averaged Navier-Stokes (RANS) equations in the Cartesian coordinate system are employed, as outlined by (Man et al 2019):…”
Section: Reynolds Average Navier-stokesmentioning
confidence: 99%
“…The results were compared with those of the experimental model of Melville Laboratory. The findings indicated that the proposed Flow-3D model was an effective tool for predicting and simulating scour depths around bridge piers and an economical method for predicting the potential outcomes.Man, C., In a subsequent study, et al [28] investigated the impact of distinct turbulence modes on the formation of bridge pier scour pits within the Flow-3D software. The simulated scour results were found to diverge significantly from the observed data collected from previous literature, due to the non-applicability of the meshing method in the Flow-3D software.…”
Section: Preprintsmentioning
confidence: 99%
“…In contrast, the LES model showed acceptable values of R 2 , while the NSE (0.423) was found to be less than RNG K-model. The deviation in scour profile by LES can be due to (1) the LES model being mesh-dependent, which requires finer cell size in the turbulent flow zones to capture the small scale fluctuations, i.e., turbulent eddies, and (2) within the scour hole, strong vertexes are generated, for which the model employed a sub-grid turbulence model, which captured small eddies in the scour hole and consequently increased the scour depth and overall retrogression on the downside of the sediment bed, as stated by Man et al [56] and Hamid et al [57]. In contrast, due to the limitation in computing the wake velocities in the shear region, the RNG K-model predicted less scour in the scour hole and on the downward areas.…”
Section: Model Verification and Validationmentioning
confidence: 99%